EFL CASCADING KNOWLEDGE AMONG ENGLISH TEACHERS AT PUBLIC AND PRIVATE HIGH SCHOOLS IN NORTH BINTAN DISTRICT - YOFFIE KHARISMA DEWI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2024)
This research study investigated the implementation and impact of cascading knowledge initiatives in EFL education among English teachers in public and private high schools in North Bintan district. Through qualitative descriptive methodology and interviews with 8 English teachers, the study aimed to uncover current practices, challenges, perceptions, and ways to enhance cascading knowledge initiatives in EFL education. The findings revealed disparities between public and private school teachers in participating in such initiatives, with facilitating factors including professional development programs, collaboration opportunities, resource accessibility, and school management support, while hindering factors encompassed constraints in time, resources, incentives, and support. The study suggests that cascading knowledge initiatives have the potential to advance teachers' professional growth and enhance the quality of EFL education, emphasizing the need for further research to delve into the determinants of successful cascading knowledge programs and their influence on student learning outcomes.